(untitled) (Journal of Imam Al-Kadhim College, 2023)
Abstract: The discussion of words and what is learned from them is an important foundation and pillar for scholars of the science of jurisprudence, because of its close connection with the jurisprudential jurisprudence, that jurisprudence that derives its material and basic issues from the speeches and texts of the Holy Qur’an and the noble Sunnah. For the essential needs of the servants: First: Extracting and deducing legal rulings from religious discourses. Second: Diagnosing the practical rules when we are ignorant of the ruling. He is interested in explaining the theories related to reading the phenomena of these legal discourses and understanding them explicitly, through the diversity of understanding the visions of the theories and discussing them seriously. The purpose of all this is to take the best of the meanings and the closest to the intention of the legislator, and we do not exaggerate when we say that the strength and importance of jurisprudence is based on what the jurist reaches from the results of the research in the phenomena of legal discourses.